Don't look at me like that : poems - Abu, Eugenia (Ibadan, Nigeria : Kraft Books Limited, 2009)
The book tells bold honest stories of beliefs and experiences... difficult and pleasant aspects of our lives but... full of acceptance and hope...told in fresh ways that evoke deep feeling from the reader.
osc 18/09/13
Loans
Keywords: Poetry; Nigeria